2008
DOI: 10.1111/j.1460-2695.2007.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life prediction of vulcanized natural rubber under proportional and non‐proportional loading

Abstract: To investigate the multiaxial fatigue properties of vulcanized natural rubber (NR), a series of tests including both proportional and non‐proportional loading paths on small specimens were performed. The existing fatigue life prediction approaches are evaluated with life data obtained in the tests. It is shown that the equivalent strain approach presents a good prediction of the fatigue life although it has a certain shortcoming. Compared with the strain energy density (SED) model, the cracking energy density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…While Fatemi and Socie (FS) [16] built their work on this model but proposed that the normal strain term should be replaced by normal stress so as to account for the effect of mean stress. This approach has been proven effective for a variety of materials [29][30][31][32]. For materials showing normal fracture, Smith et al (SWT) [18] suggested that the maximum normal strain plane should be considered as the critical plane.…”
Section: Introductionmentioning
confidence: 99%
“…While Fatemi and Socie (FS) [16] built their work on this model but proposed that the normal strain term should be replaced by normal stress so as to account for the effect of mean stress. This approach has been proven effective for a variety of materials [29][30][31][32]. For materials showing normal fracture, Smith et al (SWT) [18] suggested that the maximum normal strain plane should be considered as the critical plane.…”
Section: Introductionmentioning
confidence: 99%
“…According the stress-strain curve fitting of the experimental data, the curve significantly changed during the first five load cycles, especially for the cycle between the first and the second, the stress rapidreduceand gradually got stable in the next cycles, as shown in fig 2, the phenomenon of cyclic stress softening was called Mullins effect, which was a quite important issue for finite element analysis and fatigue failure criteriachoice of rubber components [6].…”
Section: Experimental Program a Materials And Specimensmentioning
confidence: 99%
“…In this paper, the three‐term Ogden model is used to express the strain energy density function as W=truetrue∑i=1Nμiαi()λ1αi+λ2αi+λ3αi3 where λ 1 , λ 2 and λ 3 are principal stretches and μ i and α i are material properties of the elastomer. Table lists the mechanical properties of an Ogden hyperelastic material as suggested by Wang et al The properties of elastomers considering the Mullins effect are estimated by comparing the stress values between the initial stage and the stabilized stage in the uniaxial fatigue tests performed by Wang et al Because stress linearly depends on μ i , in the Ogden model, a scale factor is applied to μ i in order to consider the Mullins effect.…”
Section: Properties Of Elastomers For Fatigue Predictionmentioning
confidence: 99%